Albumin competitively inhibits glycation of less abundant proteins - Bhonsle, Hemangi S.; Singh, Sameer Kumar; Srivastava, Ghanshyam; Boppana, Ramanamurthy; Kulkarni, Mahesh J. (Protein and Peptide Letters, 2008)
Glycation, a non-enzymatic reaction between glucose and protein is the primary cause of diabetic complications. Albumin, the most abundant plasma protein undergoes glycation both in vivo and in vitro. The influence of albumin on glycation of less abundant proteins has not been addressed. For the first time, we show that albumin competitively inhibits the glycation of less abundant proteins. This study suggests that at least in the initial stages of diabetes, albumin may protect other proteins from glycation.
Keywords: Diabetes; glucose; insulin; MALDI-TOF-MS; vascular complication

Analysis of AGE modified proteins and RAGE expression in HER2/neu negative invasive ductal carcinoma - Korwar, Arvind M.; Bhonsle, Hemangi S.; Chougale, Ashok D.; Kote, Sachin S.; Gawai, Kachru R.; Ghole, Vikram S.; Koppikar, Chaitanyananda B.; Kulkarni, Mahesh J. (Biochemical and Biophysical Research Communications, 2012)
Cancer is associated with increased glycolysis and carbonyl stress. In view of this, AGE modified proteins were identified from clinical breast cancer tissue using 2DE-immunoblot and mass-spectrometry. These proteins were identified to be serotransferrin, fibrinogen gamma chain, glycerol-3-phosphate dehydrogenase, lactate dehydrogenase, annexin II, prohibitin and peroxiredoxin 6, which have established role in cancer. Further, RAGE expression and its downstream signaling proteins NADPH oxidase and NF-kB were studied. Role of these AGE modified proteins and RAGE signaling in breast cancer is discussed. (C) 2012 Elsevier Inc. All rights reserved.
Keywords: advanced glycation end products; Breast cancer; RAGE

Arsenomics of exiguobacterium sp PS (NCIM 5463) - Sacheti, Poonam; Bhonsle, Hemangi S.; Patil, Rajendra; Kulkarni, Mahesh J.; Srikanth, Rapole; Gade, Wasudeo N. (RSC Advances, 2013)
In the present study, arsenate [As(V)] tolerant organisms were isolated from a metal contaminated site, and identified by 16S rDNA sequencing as Exiguobacterium sp. Arsenomics (omics of arsenic response) in Exiguobacterium sp. PS via two-dimensional gel electrophoresis (2-DGE) coupled with identification of proteins using MALDI-TOF MS, MALDI-TOF MS/MS and LC/MSE are studied vide this paper. Out of 2460 Coomassie stained proteins, 270 were differentially expressed (p < 0.05). Considering the resolution and abundance level, 45 spots (proteins) were subjected to MALDI-TOF MS/MS, MALDI-TOF/TOF and LC/MSE. Out of these, 33 were identified and categorized into several functional categories (including both known and novel/putative stress responsive proteins) viz., carbohydrate and energy metabolism, stress response, motility, amino acid, and purine and protein synthesis. The identifications of unique proteins, phosphate ABC transporter ATPase subunit and pyridine nucleotide disulfide oxidoreductase, are the significant findings of the present study which may be used as markers of As(V) stress in Exiguobacterium sp. PS. The absence of As(V) reductase activity and non-amplification of the arsC gene of the ars operon suggests that the classical mechanism of As(V) resistance may not be operating in Exiguobacterium sp. PS. Lastly, considering the fact that proteomic studies under As(V) stress were performed only in Gram negative organisms, this study is the first comprehensive endeavour to explore the mechanism of As(V) response in Gram positive organisms, Exiguobacterium sp. PS at the proteomic level.